216 Thermoregulatory and physiological responses of sows at different reproductive stages exposed to increasing ambient temperature. (30th November 2020) - McConn, Betty R; Duttlinger, Alan W; Kpodo, Kouassi R; Maskal, Jacob M; Gaskill, Brianna N; Schinckel, Allan P; Green-Miller, Angela R; Lay, Donald C; Johnson, Jay S
Abstract: Pregnant sows, especially during late-gestation, may be susceptible to heat stress due to increased metabolic heat production and body mass. Therefore, the study objective was to determine the thermoregulatory and physiological responses of sows exposed to increasing ambient temperature (TA ) at 3 reproductive stages. In 3 repetitions, 27 multiparous sows (parity 3.22±0.89) were individually housed and had jugular catheters placed 5.0±1.0 d prior to the experiment. To differentiate between reproductive stages, sows were categorized as open (not pregnant, n=9), mid-gestation (59.7±9.6 days pregnant, n=9), or late-gestation (99.0±4.8 days pregnant, n=9). During the experiment, sows were exposed to 6 consecutive 1 h periods of increasing TA (period 1, 14.39±2.14°C; period 2, 16.20±1.39°C; period 3, 22.09±1.87°C; period 4, 26.34±1.39°C; period 5, 30.56±0.81°C; period 6, 35.07±0.96°C), with 1 h transition phases in between each period. Respiration rate (RR), heart rate (HR), skin temperature, and vaginal temperature (TV ) were measured every 20 min and the mean was calculated for each period. At the end of each period, blood gases, leukocytes, and red blood cell counts were measured. Overall, RR and HR were greater (P≤0.04; 45.6% and 12.9%, respectively) in late-gestation versus mid-gestation sows. Compared to mid-gestation and open sows, TV tended to be greater (P=0.06) during period 4 (0.18°C and 0.29°C, respectively) and period 5 (0.14°C and 0.18°C, respectively) in late-gestation sows. Blood O2 increased (P< 0.01; 18.1%) for all sows with advancing period, regardless of reproductive stage. Late-gestation sows had reduced (P=0.02; 16.1%) blood CO2 compared to mid-gestation sows, regardless of period. In summary, late-gestation sows appear to be more sensitive to increasing TA as indicated by increased RR, HR, TV, and blood O2, and reduced blood CO2 when compared to mid-gestation or open sows. This change in O2 and CO2, due to increasing RR and heat stress sensitivity of late-gestation sows, may suggest an alteration to the acid-base balance, leading to respiratory alkalosis.